(untitled) (Olhar de Professor, 2025)
The aim of this research is to analyze how the relations between plane and spatial geometric figures are presented in the collection “A Conquista da Matemática” (FTD). Based on a qualitative nature with a documental design, the organization of the data was guided by an adaptation of Bardin’s Content Analysis. The analysis was guided by van Hiele’s Theory and Duval’s Theory of Semiotic Representation Registers, which brings originality to the research carried out. The results revealed that the proposed activities involving plane and spatial geometric concepts are presented succinctly in volumes six and nine of the collection, a factor which implies, according to the levels of van Hiele’s model, an interruption in the development of the student’s geometric thinking. This study also identified that the discursive and figurative treatments are not always presented simultaneously and interactively, which can interfere with understanding and, therefore, student learning.